An Overview of Junior High School Students’ Knowledge and Preparedness in Facing Natural Disasters : Original Article - Hidayati, Nur; Sholikhah, Mar'atus; Hanafi , Aprelia Afidatul; Othman, Hamidah (Babali Nursing Research, 2024)
Introduction: Glagah is one of the districts in Lamongan Regency with a high potential for natural disasters such as floods, tornadoes, droughts, and forest fires. To reduce the impact of disasters, disaster mitigation is required. On the other hand, students are a vulnerable group to natural disasters. Before disaster mitigation is carried out, it is necessary to initially identify students’ level of disaster knowledge and preparedness. The purpose of the study was to determine students’ knowledge and preparedness in facing natural disasters. Method. The study used descriptive quantitative research with a sample of 310 junior high school students in Glagah District who were obtained using a two-stage cluster random sampling technique on March 6-10, 2024. The data were collected using a questionnaire on knowledge and preparedness for floods, tornadoes, and fires, and then analyzed descriptively. Result. The results indicated that students’ knowledge in dealing with floods, tornadoes, and fires was in the "good" category (96.5%; 87.4%; 71.6%). Students were in the "prepared" category for floods and fires (62.6%; 49.7%), and in the "very prepared" category for tornadoes (48.7%). Conclusion. Students demonstrated the best knowledge in flood and fire disasters. Students were in the "very prepared" category in tornado disasters, and in the "prepared" category in floods and fires. It is recommended that future researchers can conduct interventions to improve student preparedness in all types of natural disasters and identify students’ knowledge and preparedness in dealing with earthquake disasters.